2022
DOI: 10.1063/5.0080040
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for photon unfolding spectroscopy of protein ions in the gas phase

Abstract: In this study, a new experimental method for photon unfolding spectroscopy of protein ions based on a Fourier transform ion cyclotron resonance (FT ICR) mass spectrometer was developed. The method of short-time Fourier transform has been applied here to obtain decay curves of target ions trapped in the cell of the FT ICR mass spectrometer. Based on the decay constants, the collision cross sections (CCSs) of target ions were calculated using the energetic hard-sphere model. By combining a tunable laser to the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This decay constant along with the ion’s path length ( l ) and frequency ( f 0 ) may be used to calculate CCS as shown in eq . N ( t ) = N normalo normale c t σ = c l f 0 N A similar concept was implemented experimentally on an FT-ICR platform, demonstrating the measurements of CCSs of ubiquitin that matched closely to values determined by IM. This type of CCS method was also successfully used to monitor the unfolding of protein ions following irradiation by a tunable IR laser in an FT-ICR system . Recently, the time-domain decay rate method was demonstrated experimentally on an Orbitrap mass analyzer, facilitated by development of a computational method termed direct decay profile fitting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decay constant along with the ion’s path length ( l ) and frequency ( f 0 ) may be used to calculate CCS as shown in eq . N ( t ) = N normalo normale c t σ = c l f 0 N A similar concept was implemented experimentally on an FT-ICR platform, demonstrating the measurements of CCSs of ubiquitin that matched closely to values determined by IM. This type of CCS method was also successfully used to monitor the unfolding of protein ions following irradiation by a tunable IR laser in an FT-ICR system . Recently, the time-domain decay rate method was demonstrated experimentally on an Orbitrap mass analyzer, facilitated by development of a computational method termed direct decay profile fitting .…”
Section: Introductionmentioning
confidence: 99%
“…This type of CCS method was also successfully used to monitor the unfolding of protein ions following irradiation by a tunable IR laser in an FT-ICR system. 28 Recently, the timedomain decay rate method was demonstrated experimentally on an Orbitrap mass analyzer, facilitated by development of a computational method termed direct decay profile fitting. 12 In essence, Fourier transformation of the transient data followed by inverse FT allowed the final time-domain data to be fit to an exponential decay model to determine the decay rate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Subsequently, the decay time constants of PT3 and PT5 before and after oxidation were calculated by eq S1. 48 By using the decay time constant, the cross section (Å 2 ) of PT3, PT3 + Fe 3+ , PT5, and PT5 + Fe 3+ were calculated according to eq S2, 48 and the results showed that Å 2 PT3 > Å 2…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First, the mass spectra of PT3 and PT5 before and after oxidation were obtained through Fourier transform ion cyclotron resonance (FT ICR) (Figure S41 and Supporting Information). Subsequently, the decay time constants of PT3 and PT5 before and after oxidation were calculated by eq S1 . By using the decay time constant, the cross section (Å 2 ) of PT3, PT3 + Fe 3+ , PT5, and PT5 + Fe 3+ were calculated according to eq S2, and the results showed that Å 2 PT3 > Å 2 PT3+Fe 3+ and Å 2 PT5 > Å 2 PT5+Fe 3+ (Figure S42, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation